Visceral Hypersensitivity Is Provoked by 2,4,6-Trinitrobenzene Sulfonic Acid-Induced Ileitis in Rats - Shah, Manoj K.; Wan, Juan; Janyaro, Habibullah; Tahir, Adnan H.; Cui, Luying; Ding, Ming-Xing (Frontiers in Pharmacology, 2016)
Background and Aims: Crohn’s Disease (CD), a chronic Inflammatory Bowel Disease, can occur in any part of the gastrointestinal tract, but most frequently in the ileum. Visceral hypersensitivity contributes for development of chronic abdominal pain in this disease. Currently, the understanding of the mechanism underlying hypersensitivity of Crohn’s ileitis has been hindered by a lack of specific animal model. The present study is undertaken to investigate the visceral hypersensitivity provoked by 2,4,6-trinitrobenzene sulfonic (TNBS)-induced ileitis rats. Methods: Male Sprague-Dawley rats were anaesthetized and laparotomized for intraileal injection of TNBS (0.6 ml, 80 mg/kg body weight in 30% ethanol, n = 48), an equal volume of 30% Ethanol (n = 24) and Saline (n = 24), respectively. Visceral hypersensitivity was assessed by visceromotor responses (VMR) to 20, 40, 60, 80 and 100 mmHg colorectal distension pressure (CRD) at day 1, 3, 7, 14, 21 and 28. Immediately after CRD test, the rats were euthanized for collecting the terminal ileal segment for histopathological examinations and ELISA of myleoperoxidase and cytokines (TNF-α, IL-1β, IL-6), and dorsal root ganglia (T11) for determination of calcitonin gene-related peptide by immunohistochemistry, respectively. Results: Among all groups, TNBS-treatment showed transmural inflammation initially at 3 days, reached maximum at 7 days and persisted up to 21 days. The rats with ileitis exhibited (P < 0.05) VMR to CRD at day 7 to day 21. The calcitonin gene-related peptide-immunoreactive positive cells increased (P < 0.05) in dorsal root ganglia at day 7 to 21, which was persistently consistent with visceral hypersensitivity in TNBS-treated rats. Conclusions: TNBS injection into the ileum induced transmural ileitis including granuloma and visceral hypersensitivity. As this model mimics clinical manifestations of CD, it may provide a road map to probe the pathogenesis of gut inflammation and visceral hypersensitivity, as well as for establishing the therapeutic protocol for Crohn’s ileitis.